Hydrogel-By-Design: Smart Delivery System for Cancer Immunotherapy - Cui, Rongwei; Wu, Qiang; Wang, Jing; Zheng, Xiaoming; Ou, Rongying; Xu, Yunsheng; Qu, Shuxin; Li, Danyang (Frontiers in Bioengineering and Biotechnology, 2021)
Immunotherapy has emerged as a promising strategy for cancer treatment, in which durable immune responses were generated in patients with malignant tumors. In the past decade, biomaterials have played vital roles as smart drug delivery systems for cancer immunotherapy to achieve both enhanced therapeutic benefits and reduced side effects. Hydrogels as one of the most biocompatible and versatile biomaterials have been widely applied in localized drug delivery systems due to their unique properties, such as loadable, implantable, injectable, degradable and stimulus responsible. Herein, we have briefly summarized the recent advances on hydrogel-by-design delivery systems including the design of hydrogels and their applications for delivering of immunomodulatory molecules (e.g. cytokine, adjuvant, checkpoint inhibitor, antigen), immune cells and environmental regulatory substances in cancer immunotherapy. We have also discussed the challenges and future perspectives of hydrogels in the development of cancer immunotherapy for precision medicine at the end.